The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ana.25153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for disorders of arousal: A video‐polysomnographic assessment

Abstract: Frequent slow/mixed arousals in SWS and complex behaviors during vPSG are strongly associated with DOAs, and could be promising biomarkers for the diagnosis of non-rapid eye movement parasomnias. Ann Neurol 2018;83:341-351.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 30 publications
3
52
1
Order By: Relevance
“…During N3 sleep, spontaneous startles were associated with sleep terrors and persistent slow postarousal EEG activity, a pattern typically observed in disorders of arousal (DOA), these parasomnias being previously reported in hyperekplexia patients. Both sisters were just above the slow/mixed arousal index but below the threshold of slow wave sleep fragmentation index for DOA . Other motor behaviors involving the face and the upper limbs were found in REM sleep, together with increased phasic and tonic chin mentalis EMG activities in both patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…During N3 sleep, spontaneous startles were associated with sleep terrors and persistent slow postarousal EEG activity, a pattern typically observed in disorders of arousal (DOA), these parasomnias being previously reported in hyperekplexia patients. Both sisters were just above the slow/mixed arousal index but below the threshold of slow wave sleep fragmentation index for DOA . Other motor behaviors involving the face and the upper limbs were found in REM sleep, together with increased phasic and tonic chin mentalis EMG activities in both patients.…”
Section: Discussionmentioning
confidence: 76%
“…Sleep stages, microarousals, periodic limb movements, and respiratory events were scored manually according to standard criteria. A particular attention was paid to motor behaviors, tonic and phasic chin muscle activities during REM sleep, and N3 sleep fragmentation . Results were compared to normative values obtained in 15 healthy controls (10 males, median age 24 years, range 19–30 years).…”
Section: Case Seriesmentioning
confidence: 84%
“…Some EEG markers (hypersynchronous delta sleep activities and spectral analysis) lack specificity, but recently, an index of arousals plus awakenings (greater than 6.8 per N3 time) has proven sensitive (79%) and specific (82%) for distinguishing patients referred for DOA from healthy participants. 6 A slow/mixed arousal index (greater than 2.5 per N3 time) was even more sensitive (94%) and totally specific (100%). However, this analysis requires highly trained sleep scorers and 8 EEG channels.…”
Section: Introductionmentioning
confidence: 94%
“…Although this occurrence is rare [91], the ICSD-3 [5] states that when PSG does identify arousals out of N3 sleep (usually in the form of confusional arousal, very rarely out-of-bed attempts), this can be considered a contributing factor to the clinical diagnosis of NREM parasomnias. A number of recent studies reported, somewhat surprisingly, episodes of NREM parasomnias in roughly 60% of the monitored patients during a night of PSG monitoring [92,93]. It remains unclear why some studies find a low prevalence of episodes during laboratory PSG assessments, while others find a high prevalence.…”
Section: Diagnosing Nrem Parasomniasmentioning
confidence: 99%